Connective tissue disease-associated interstitial lung disease – A multicenter observational study from India - Sham Santhanam; Pravin Patil; Mohit Goyal; C B Mithun; Parthajit Das; Kavitha Mohanasundaram; Neeraj Jain; Vijaya Prasanna; Keerthi Talari; Himanshu Pathak; Parshant Aggarwal; Deepika Ponnuru; et al. (Indian Journal of Rheumatology)
Objectives: The objectives of the study were to study the demographic, clinical, serological, and imaging characteristics of connective tissue disease-associated interstitial lung disease (CTD-ILD) patients seen at rheumatology centers across India. Methods: Adult outpatients with CTD-ILD and interstitial pneumonia with autoimmune features (IPAF), who were seen at the 12 participating rheumatology centers at least once in the preceding 6 months, were recruited and information was retrieved from their medical records. Information on demographics, duration of symptoms, diagnosis, comorbidities, autoantibodies, lung imaging, pulmonary function testing (PFT), echocardiography (ECHO), treatment, immunization, and admissions for exacerbations was obtained. Results: A total of 620 patients (505 women) were recruited. Rheumatoid arthritis (RA) was the most common CTD associated with ILD followed by systemic sclerosis and mixed connective tissue disorder. In our cohort, 372 (60%) patients had not received a diagnosis of their rheumatic disease or the ILD before seeing their rheumatologist. High-resolution computed tomography of the chest was available for 551 (88.9%) of the patients, and 327 (59.3%) had a nonspecific interstitial pneumonitis (NSIP) pattern. PFT and ECHO data were available for 437 (70.5%) and 453 (73.1%) patients, respectively. The mean forced vital capacity was 61.89% ± 14.8% of the predicted. Pulmonary hypertension (PH) was detected in 162 (35.8%) patients. The most common immunosuppressive used for lung disease was mycophenolate mofetil (54.0%) followed by azathioprine (19.5%). Medical records of these patients showed that after a diagnosis of ILD, in 79 patients, methotrexate (MTX) was changed to an alternative drug, whereas in 11 patients, MTX was added by the rheumatologist after diagnosing the CTD-ILD. There were 28 patients with IPAF. Mycophenolate and rituximab were the common drugs used in IPAF patients. Only 36 (5.8%) of the 620 patients were vaccinated with influenza as well as both the conjugate and the polysaccharide pneumococcal vaccines. Seventy-four (12.25%) patients had a history of one or more admissions for acute exacerbations or complications of ILD. Conclusion: In this study, RA-ILD was the most common CTD and NSIP was the predominant ILD pattern on high-resolution computerized tomography. More than a third of the patients had PH. In the real-life scenario, we noticed hesitancy among the treating doctors in using MTX in RA-ILD. The number of patients with complete influenza and pneumococcal vaccination was low and this issue needs to be specifically addressed. Larger prospective registry-based data are needed to understand CTD-ILD and the unmet needs in the Indian context.